Impacts of climate change on climatically suitable regions of two invasive Erigeron weeds in China - Huang, Yumeng; Zhang, Guoliang; Fu, Weidong; Zhang, Yue; Zhao, Zihua; Li, Zhihong; Qin, Yujia (Frontiers in Plant Science, 2023)
Introduction Erigeron philadelphicus and Erigeron annuus are two ecologically destructive invasive plants from the Asteraceae family. Predicting the potential distribution pattern of two invasive alien Erigeron weeds can provide a scientific basis for prevent the further spread of these two weeds in China under climate change. Methods Based on historical occurrence datasets and environmental variables, we optimized a MaxEnt model to predict the potential suitable habitats of E. philadelphicus and E. annuus. We also analyzed the shifts of distribution centroids and patterns under climate change scenarios. Results The key variables that affect the potential geographical distribution of E. annuus and E. philadelphicus, respectively, are temperature seasonality and precipitation of the driest month. Moreover, topsoil sodicity and topsoil salinity also influence the distribution of E. philadelphicus. Under climate change, the overall suitable habitats for both invasive alien Erigeron weeds are expected to expand. The potential geographical distribution of E. annuus exhibited the highest expansion under the SSP245 climate scenario (medium forcing scenarios), whereas E. philadelphicus had the highest expansion under the SSP126 climate scenario (lower forcing scenarios) globally. The future centroid of E. annuus is projected to shift to higher latitudes specifically from Hubei to Hebei, whereas E. philadelphicus remains concentrated primarily in Hubei Province. The overlapping suitable areas of the two invasive alien Erigeron plants mainly occur in Jiangsu, Zhejiang, Fujian, Jiangxi, Hunan, Guizhou, and Chongqing, within China. Discussion Climate change will enable E. annuus to expand into northeastern region and invade Yunnan Province whereas E. philadelphicus was historically the only suitable species. E. annuus demonstrates a greater potential for invasion and expansion under climate change, as it exhibits higher environmental tolerance. The predictive results obtained in this study can serve as a valuable reference for early warning systems and management strategies aimed at controlling the spread of these two invasive plants.